OECD Science, Technology and Industry Scoreboard 2017 – The digital transformation - Editors, (New Zealand Science Review, 2017)
​The OECD Science, Technology and Industry Scoreboard 2017 draws on the latest international comparative data to uncover the strength of the OECD and other large economies, and shows how the digital transformation is affecting science, innovation, the economy and the way people work and live. Mobility, cloud computing, the Internet of Things (IoT), artificial intelligence (AI) and big data analytics are among the most important technologies in the digital economy today, empowering businesses, consumers, and society as a whole. However, their development and use are distributed very unevenly. The headquarters of the top 2,000 R&D corporations worldwide are concentrated in just a few economies – notably the United States, Japan, and China – and about 70% of their total R&D spending is concentrated in the top 200 firms. Although the digital transformation is affecting all sectors of the economy, Telecommunications and IT services are consistently ahead in terms of digital intensity, while Agriculture, Mining, and Real estate are consistently ranked at the bottom. Significant differences remain in a majority of OECD countries, including between younger and older generations, between women and men, by educational background, urban and local locations, and firms of different size. This publication aims to help governments design more effective science, innovation, and industry policies in the digital era.